The Political Map of the World and its Specific Features - Eshmamatovich, Boymatov Bahrom (Indonesian Journal of Innovation Studies, 2022)
The article discusses the world political map and its specific aspects, including quantitative changes in the world political map, qualitative changes, political and geographical changes on the map, evolutionary, revolutionary, military -Political conditional changes are briefly studied.